Pens, swords, and the springs of art the oral poetry dueling of Palestinian weddings in Galilee - Yaqub, Nadia G. (Brill studies in Middle Eastern literature, 2007)
"Offering a detailed analysis of oral poetry dueling performed at traditional Palestinian weddings, this work is unique in addressing poetry dueling as a performative and compositional device, and exploring the complex linkages between this tradition and other genres of Arabic poetry. It includes a study of poetry dueling in standard Arabic; a description of the historical and performance contexts of the Palestenian duels, as well as of poets and their training; an analysis of a single performance; and a reinterpretation of the nature of verbal dueling generally. Including a transcription and translation of an entire performance, the book considers the social efficacy of poetry dueling, its aesthetic nature, and its value as a compositional device within a larger system of poetic production".